PERAN HAKIM SEBAGAI PEMBARU HUKUM - Chandra, Alex (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
In Indonesia, the legal system adheres to the European continental system, which is a legacy of the legal system inherited from the Netherlands, which once colonized Indonesia and thus had a significant influence on the country's legal system. Within the framework of the Continental European legal system, judges play a crucial role in adjudicating cases and ensuring justice for all parties involved. According to the Judicial Power Law, judges are prohibited from rejecting a case and are expected to possess a comprehensive knowledge of the law. Therefore, in addition to upholding justice, judges must also be capable of creating or discovering legal principles This research employs a qualitative approach to explore the role of judges as legal innovators within Indonesia's judicial system. It concludes that in the European continental system, judges hold a highly significant position in legal innovation, which, in this context, pertains to law enforcement. In fulfilling their duties, judges must uphold values such as independence, morality, and justice to render fair judgments, aligning with the ultimate aspiration of the legal system..